Analysis Of Green Marketing Tourism Village-Based Tourism Green Satisfaction Towards Green Loyalty - Elfitra Desy Surya; Firman Ario (International Journal of Management, Economic and Accounting, 2023)
This research was carried out in the village tourism Kota Pari Serdang Bedagai where this study was conducted to determine how the influence of the service marketing mix consists of Green Products (X1), Green Price (X2), Green Promotion (X3), Green Place (X4) and green satisfaction (Z) as mediated variable and green loyalty (Y). The population in this study was consumers with 240 samples taken. The research was conducted from October to December 2023. This study used quantitative data which was processed using SEM-PLS analysis model with Smart PLS 3.0. application. Data sources used primary data taken directly from respondents and secondary one was obtained from interviews with travelers visiting Kota Pari village. The results of the research show that green products, green prices, green promotions, and green places, have a positive and significant effect on green loyalty to visiting Kota Pari village. Meanwhile, green satisfaction in this research can mediate the influence of green products, green prices, green promotions, green places, and travelers visiting Kota Pari Village.